Complex Carbocyclic Skeletons from Aryl Ketones through a Three‐Photon Cascade Reaction. (30th January 2020) - Næsborg, Line; Jandl, Christian; Zech, Andreas; Bach, Thorsten
Abstract: Starting from readily available 7‐substituted 1‐indanones, products with a tetracyclo[5.3.1.0 1, 7 0 4, 11 ]undec‐2‐ene skeleton were obtained upon irradiation at λ =350 nm (eight examples, 49–67 % yield). The assembly of the structurally complex carbon framework proceeds in a three‐photon process comprising an ortho photocycloaddition, a disrotatory [4π] photocyclization, and a di‐π‐methane rearrangement. The flat aromatic core of the starting material is converted into a functionalized polycyclic hydrocarbon with exit vectors in three dimensions. Ring opening reactions at the central cyclopropane ring were explored, which enable the preparation of tricyclo[5.3.1.0 4, 11 ]undec‐2‐enes and of tricyclo[6.2.1.0 1, 5 ]undecanes. Abstract : Den Gipfel erklommen : Eine wesentliche Bindungsreorganisation überführt das markierte Aren‐C‐Atom aus der „Ebene" zum Gipfel dreidimensionaler Kohlenwasserstoff‐„Hügel". Drei Photonen initiieren eine Kaskadenreaktion zur Umwandlung des flachen aromatischen Kerns der Startmaterialien in funktionalisierte, pentacyclische Kohlenwasserstoffe (elf Beispiele; 37–67 %), die zu weiterer Ringöffnung in situ oder über einen zweistufigen Prozess neigen.